Pre-treatment nutrition-related indicators and the prognosis of patients with newly diagnosed epithelial ovarian cancer: an ambispective cohort study - Wang, Shirui; Zhu, Jingyu; Wu, Ningjuan; Wang, Nannan; Dang, Xiaohe; Zhao, Minyi; Zhao, Juan; Ma, Ding; Yang, Xiaofeng (Frontiers in Nutrition, 2025)
BackgroundFew studies have explored the link between nutritional status and prognosis in patients with epithelial ovarian cancer (EOC), and existing findings are controversial. Thus, this study aimed to explore the effects of pre-treatment nutrition-related indicators on the prognosis of patients with newly diagnosed EOC.MethodsIn this ambispective cohort study, 1,020 patients with EOC diagnosed by pathology examination were enrolled and followed-up until December 31, 2023. Univariate and multivariable analyses were conducted on nutrition-related indicators, including body mass index (BMI), albumin (ALB), hemoglobin (Hb), diabetes mellitus (DM), and hyperlipidemia, along with clinicopathological characteristics that might affect patients’ first-line chemotherapy response, progression-free survival (PFS), and overall survival (OS). Survival curves were created using the Kaplan–Meier method. A Cox proportional hazards model was established to obtain hazard ratios (HRs) and 95% confidence intervals (CIs).ResultsThe median follow-up duration was 48 months. Compared with patients having normal nutritional indicators, those with hypoalbuminemia had poorer first-line chemotherapy responses. The proportions of those with complete response (CR), partial response (PR), and stable disease or progressive disease (SD/PD) for the ≤30 g/L, 30 < ALB<35 g/L and normal ALB groups were 57.2, 20.6, and 22.2% vs. 62.0, 22.5, and 15.5% vs.79.5, 13.6, and 6.9%. Patients with hypoalbuminemia had shorter median PFS (mPFS): 15 vs. 19 vs. 57 months in the three groups, respectively; and shorter median OS (mOS): 36 vs. 51 vs. 124 months. Patients with hyperlipidemia also exhibited poorer first-line chemotherapy responses; CR, PR, and SD/PD rates for the hyperlipidemia and non-hyperlipidemia groups were 68.9, 19.5, and 11.6% vs. 76.4, 14.7, and 8.9%, respectively, and shorter mPFS (17 vs. 57 months) and mOS (40 vs. 119 months). Patients with anemia had poorer first-line chemotherapy responses; CR, PR, and SD/PD rates for the anemia and non-anemia groups were 68.4, 19.7, and 11.9% vs. 76.2, 14.9, and 8.9%, respectively. All differences were statistically significant (p < 0.05). Multivariable analysis identified hyperlipidemia as an independent risk factor for PFS (hazard ratio [HR] = 2.083; 95% CI:1.726–2.514; p < 0.001) and OS (HR = 2.158; 95% CI:1.746–2.666; p < 0.001), whereas hypoalbuminemia and anemia were not confirmed as independent prognostic factors. This study found no effect of BMI or DM on patient prognosis.ConclusionPre-treatment hypoalbuminemia, hyperlipidemia, and anemia negatively affected the prognosis of patients with newly diagnosed EOC, with hyperlipidemia being an independent risk factor for shorter survival.